Changes in Properties of Muffins Incorporated with Emblica officinalis Fruit Osmodehydrated with Fructooligosaccharide. Issue 2 (22nd June 2016) - Nambiar, Sinjitha S.; Ashwini,; Shetty, Nandini Prasad; Ravi, R.; Prabhasankar, P.
Abstract: Muffin preparation using Emblica officinalis fruits was done by incorporation of fructooligosaccharide (FOS) infused E. officinalis fruits (FOS ‐ Emblica) in proportions of 5%, 10% and 15% in wheat flour. Antioxidant and atherosclerotic foam cell inhibition assays showed that 10% and 15% FOS‐Emblica muffins had higher bioactivity than that of 5% FOS‐Emblica muffins and control muffins. Phenolic and flavonoid compounds present in untreated fruits were preserved in 10% and 15% FOS‐Emblica muffins. Texture analysis showed that addition of E. officinalis resulted in soft textured muffins with reduced hardness and gumminess and increased springiness, with these parameters showing significant difference in 10% and 15% FOS‐Emblica muffins. Sensory analysis showed that 10% FOS‐Emblica muffins had better overall quality. Practical Applications: Bakery products like muffins are fatty food stuffs that are devoid of antioxidant benefits. Incorporation of nutritious fruits like Emblica officinalis – osmodehydrated with prebiotic‐like fructooligosaccharide – into muffins not only increases its antioxidant properties but also enhances the sensory and textural qualities of muffins. It also enhances the phenolic and flavonoid concentration of muffins. Further, prebiotic‐fructooligosaccharide is also known to improve digestion.